DEVELOPMENT OF LEARNING MEDIA BASED ON LOCAL WISDOM FOR LITERACY MATERIALS AT SDN SIEM ACEH BESAR - Hendra Kasmi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to develop a learning medium based on local wisdom for literacy material at SDN SIEM, Aceh Besar, to enhance students' understanding of local culture and their literacy skills. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observations, interviews, and questionnaires administered to teachers and students. The results of the study indicate that the Acehnese folklore-based learning media in the form of animated videos successfully increased students' motivation and interest in literacy learning. This media also received excellent evaluations in terms of content quality, design, and instructional feasibility based on validations by subject matter and media experts. The implementation of the media in the classroom demonstrated a 30% improvement in students' learning outcomes compared to the period before using the local wisdom-based media. This finding highlights that integrating local wisdom into learning media can serve as an innovative alternative to support literacy education in elementary schools, particularly in the Aceh Besar region. Therefore, local wisdom-based learning media are suitable for broader implementation as part of a teaching strategy that supports character building while preserving local cultural values.